Collaborative Development of Smart Villages: A Model with Pesantren Joglo Alit for Social, Cultural, Economic, and Ecological Enhancement - Muhammad Qowim (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2023)
The research presented in this article seeks to reconstruct the concept of smart villages, focusing on the alignment with the aspirations of lecturers at the Educational Management Department at UIN Sunan Kalijaga Yogyakarta. In collaboration with Pesantren Joglo Alit, a smart public space model was developed to pioneer Smart Village, emphasizing social, cultural, economic, and ecological enhancements to support a better quality of life. Through Strengths, Opportunities, Aspirations, and Results (SOAR) analysis on two levels—academic society aspiration and mutual partner aspiration—a prototype of smart villages was constructed. The research identifies three strategic issues: smart village, star-up for education, and laboratory for social service. Several alternative models for smart village development were explored, leading to the agreement on an enterprise model in the targeted village. The prototype implementation took 41 days, and its implications offer a nuanced understanding of how education can drive broader relevant competencies in smart village development. The findings have significant implications for education, rural development, and sustainability. Constraints such as low technology are acknowledged, and recommendations for future research and policy formulation are provided.